Smart Parenting dalam Membentuk Karakter Anak pada Era Digitalisasi di Kabupaten Kubu Raya, Kalimantan Barat - Patriani, Ira; Haryaningsih, Sri; Devi Andriani, Farah; Risna Sari, Ade; Maulana, Akbar; Ananda Pratiwi, Putri (LPkM Universitas Bakrie, 2023)
Along with the times, the role of parents in helping children's growth and development so that they grow into intelligent children becomes a responsibility that must be done. However, public awareness and understanding, especially parents, do not know how to provide good parenting to children. This can lead to undirected child behavior and a lack of stable emotions. Community Service Activities (PKM) are carried out to socialize how good and correct parenting is for children, especially children with special needs at Sekolah Luar Biasa (SLB) Ibu Bahagia, Sungai Raya District, Kubu Raya Regency, Kalimantan Barat Regency. The main target of this activity is the parents/guardians of students of SLB Ibu Bahagia. The activity plan includes socialization about parenting, education about sexual harassment, and discussion sessions. The results of this activity show an increase in the understanding of participants (parents/guardians of students) in providing proper parenting and sharing knowledge about examples of improper parenting that must be avoided.